On the miscibility of cardiolipin with 1,2-diacyl phosphoglycerides: Binary mixtures of dimyristoylphosphatidylethanolamine and tetramyristoylcardiolipin - Frías, María de los Ángeles (2011)
The thermotropic phase behavior and organization of model membranes composed of binary mixtures of the quadruple-chained, anionic phospholipid tetramyristoylcardiolipin (TMCL) with the double-chained zwitterionic phospholipid dimyristoylphosphatidylethanolamine (DMPE) were examined by a combination of differential scanning calorimetry (DSC) and Fourier-transform infrared (FTIR) spectroscopy. After equilibration at low temperature, DSC thermograms exhibited by binary mixtures of TMCL and DMPE containing < 80 mol DMPE exhibit a fairly energetic lower temperature endotherm and a highly energetic higher temperature endotherm. As the relative amount of TMCL in the mixture decreases, the temperature, enthalpy and cooperativity of the lower temperature endotherm also decreases and is not calorimetrically detectable when the TMCL content falls below 20 mol%. In contrast, the temperature of the higher temperature endotherm increases as the proportion of TMCL decreases, but the enthalpy and cooperativity both decrease and the transition endotherms become multimodal. The FTIR spectroscopic results indicate that the lower temperature endotherm corresponds to a lamellar crystalline (Lc) to lamellar gel (Lβ) phase transition and that the higher temperature transition involves the conversion of the Lβ phase to the lamellar liquid-crystalline (Lα) phase. Moreover, the FTIR spectroscopic signatures observed at temperatures below the onset of the Lc/Lβ phase transitions are consistent with the coexistence of structures akin to a TMCL-like Lc phase and the L β phase, and with the relative amount of the TMCL-like L c phase increasing progressively as the TMCL content of the mixture increases. These latter observations suggest that the TMCL and DMPE components of these mixtures are poorly miscible at temperatures below the L β/Lα phase transition temperature. Poor miscibility of these two components is also suggested by the complexity of the DSC thermograms observed at the Lβ/Lα phase transitions of these mixtures and with the complex relationship between their Lβ/Lα phase transition temperatures and the composition of the mixture. Overall, our data suggests that TMCL and DMPE may be intrinsically poorly miscible across a broad composition range, notwithstanding the homogeneity of the fatty acid chains of the two components and the modest (~ 10 °C) difference between their Lβ/Lα phase transition temperatures.